Métodos e algoritmos para ajuste dos meios básicos para controle de tensão em sistemas de distribuição - Milbradt, Rafael Gressler (2007)
Nowadays, the quality of energy supplied to customers is an important aspect that must be taken into account in distribution systems analysis. The Brazilian national agency which regulates the distribution systems standards is applying punishments to the energy supplying companies which can not keep the voltage levels inside the allowed limits. Besides, in most cases, energy supplying companies are trying to improve the quality of energy without make use of large investments. The voltage control through the regulation of distribution transformers taps and transformer under load tap changer (ULTC) are being used in most of distribution systems. These types of voltage control may reduce or eliminate the condition which voltage levels exceeding the allowed limits. It is important to observe that use of estimations with few or unfaithful information about secondary networks requires appropriate methodologies. Therefore, this study uses simplified models of secondary networks which may estimate the final results, even in cases without any information. The adjustment of transformers taps is defined to reduce undervoltage in primary and secondary networks. As regards secondary networks, voltage drop are considered up to the center of load, which provides an appropriate voltage levels to the most of customers in analysis. The adjustment of ULTC uses the voltage control law, in order to complement the adjustment earlier described. In this case, the ULTC allows an automaticregulation, which provides a balance of the voltage drop variation during a day. The voltage control law considers voltage drop up to the center of load in secondary networks. Thus the substation voltage control law is calculated by the weighed mean for the power of the voltage drop until the center of load of each distribution transformer. This work also implements an indicator, called energy supplied outside the allowed limits (EFFP). This indicator allows to measure the efficiency of networks, considering voltage levels violations. Thus, it is possible to evaluate the algorithms used in this analysis. As regards the final results, the software called ASD-CT was developed to implement all the algorithms here proposed. This software uses the Java proceedings, according to modern concepts applied on software engineering. Finally, it is important to emphasize that the ASD-CT software presented excellent outputs, considering radially operated distribution networks belong to the State Company of Electric Energy (CEEE-D)